2021
DOI: 10.3390/ijerph19010185
|View full text |Cite
|
Sign up to set email alerts
|

Caregivers of Individuals with Cancer in the COVID-19 Pandemic: A Phenomenological Study

Abstract: Caregivers of individuals with cancer in the COVID-19 pandemic are faced with the demands of cancer and the health needs produced by it, along with their own health and self-care needs, and the uncertainties of expectations and risks. A qualitative analytical phenomenological study with caregivers of individuals with cancer registered at the state referral hospital supplying medications, who answered the sociodemographic assessment questionnaires and semi-structured questions about their feelings and perceptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…Results presented here, a subset of a broader mixed-methods study conducted within the context of the COVID-19 pandemic, document adverse effects of pandemic-related policies, and realities of an unpaid caregiving workforce. Themes drawn from caregiver interviews corroborate findings from previous studies in which caregivers reported heightened caregiving stresses due to their inabilities to perform complex supportive caretaking roles within the context of care visits [ 21 ], engage in shared cancer care decision-making, and seek help for their own healthcare utilization due to concerns of contracting COVID-19 while providing care for someone who was immunocompromised due to cancer [ 6 , 7 , 22 24 ].…”
Section: Discussionsupporting
confidence: 73%
“…Results presented here, a subset of a broader mixed-methods study conducted within the context of the COVID-19 pandemic, document adverse effects of pandemic-related policies, and realities of an unpaid caregiving workforce. Themes drawn from caregiver interviews corroborate findings from previous studies in which caregivers reported heightened caregiving stresses due to their inabilities to perform complex supportive caretaking roles within the context of care visits [ 21 ], engage in shared cancer care decision-making, and seek help for their own healthcare utilization due to concerns of contracting COVID-19 while providing care for someone who was immunocompromised due to cancer [ 6 , 7 , 22 24 ].…”
Section: Discussionsupporting
confidence: 73%
“…Restoring physical and social support to their assisted were seen to be the main needs. Lack in structural social policies to support patients and their families on an emotional level has probably revealed a vulnerability of the healthcare systems towards this aspect [ 26 ].…”
Section: Plasticity Of Cancer Care System During An Unprecedented Sit...mentioning
confidence: 99%